Strategi Manajemen Kepala Madrasah dalam Menanamkan Nilai-Nilai Keagamaan di Madrasah Yayasan Pendidikan MTs Al-Fajar Sei Mencirim Deli Serdang Sumatra Utara - Nadia Arifqa; Rustam Ependi (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2024)
Educational institutions are a forum or means for forming children's character. Within these religious values ??there are moral values. Schools must be able to carry out systematic planning or good management as a serious form of managing the best personality of children. This research aims to determine the Principal's Management Strategy in Instilling religious values ??in MTs Al-Fajar Sei Mencirim Education Foundation schools so that students' moral values ??are formed from Islamic activities in instilling religious values. The research method used was qualitative with a descriptive approach, by interviewing three research informants, namely the school principal and teachers. Data were analyzed using data reduction, data presentation, and conclusions and verification. The results of the research show that the management strategy carried out by the school principal in instilling religious values ??is that there are graduation requirements for MTs Al-Fajar students in the form of memorizing surahs and practicing worship. There are also routines carried out by saying hello, praying and worshiping. Supporting factors are prayer room facilities, mukena and Al-Qur'an